Impact of Aberrant Myeloid Antigen Expression on Outcomes of Patients with T-cell Acute Lymphoblastic Leukemia - Mohamed Al-Zaabi; Murtadha Al-Khabori; Naglaa Fawaz; Sulayma Al-Lamki; Arwa Al-Riyami; Mohammed Al-Huneini; Muhanna Al-Muslahi; Salam Alkindi (Oman Medical Journal, 2017)
Objectives: To evaluate the impact of myeloid antigen expression on complete remission (CR), event-free survival (EFS), and overall survival (OS) in patients with T-cell acute lymphoblastic leukemia (T-ALL) treated with intensive chemotherapy. Methods: We retrospectively reviewed consecutive patients diagnosed with T-ALL and treated in Sultan Qaboos University Hospital and Royal Hospital in Oman between 2004 and 2010. The diagnosis of T-ALL was established using French-American-British classification or World Health Organization criteria. Patients were considered having myeloid antigen expression if they expressed CD13, CD33, or both (My+ and My–). Results: Of the 39 patients, 38 were included in the study (25 patients with My– and median age of 18.4 years, 13 patients with My+ and median age of 22.0 years). Median follow-up was 12 months. Thirty-two out of the total cohort were eligible for response-rate assessment. Twenty-nine patients (90.6%) achieved CR with one or two courses of chemotherapy with similar CR rates between the two groups (p = 0.880). Twenty-five percent (5/20) of the patients with My– required two courses of induction, whereas 58.3% (7/12) of My+ required two courses of induction and the difference was statistically significant (p = 0.040). In the multivariable analysis; age, gender, initial white blood cell count, central nervous system disease, and myeloid antigen expression were not statistically significant predictors of CR. The EFS and OS were similar between the My+ and My– groups p = 0.180 and p = 0.440, respectively. Conclusions: Patients with T-ALL with myeloid antigen expression need more courses of induction; however, rates of CR, EFS, and OS are not different from those without myeloid antigen expression. Larger prospective studies are required to confirm these findings.